Comparative Chloroplast Genomics of Dipsacales Species: Insights Into Sequence Variation, Adaptive Evolution, and Phylogenetic Relationships - Fan, Wei-Bing; Wu, Ying; Yang, Jiao; Shahzad, Khurram; Li, Zhong-Hu (Frontiers in Plant Science, 2018)
In general, the chloroplast genomes of angiosperms are considered to be highly conserved and affected little by adaptive evolution. In this study, we tested this hypothesis based on sequence differentiation and adaptive variation in the plastid genomes in the order Dipsacales. We sequenced the plastid genomes of one Adoxaceae species and six Caprifoliaceae species, and together with seven previously released Dipsacales chloroplasts, we determined the sequence variations, evolutionary divergence of the plastid genomes, and phylogeny of Dipsacales species. The chloroplast genomes of Adoxaceae species ranged in size from 157,074 bp (Sinadoxa corydalifolia) to 158,305 bp (Sambucus williamsii), and the plastid genomes of Caprifoliaceae varied from 154,732 bp (Lonicera fragrantissima var. lancifolia) to 156,874 bp (Weigela florida). The differences in the number of genes in Caprifoliaceae and Adoxaceae species were largely due to the expansion and contraction of inverted repeat regions. In addition, we found that the number of dispersed repeats (Adoxaceae = 37; Caprifoliaceae = 384) was much higher than that of tandem repeats (Adoxaceae = 34; Caprifoliaceae = 291) in Dipsacales species. Interestingly, we determined 19 genes with positive selection sites, including three genes encoding ATP protein subunits (atpA, atpB, and atpI), four genes for ribosome protein small subunits (rps3, rps7, rps14, and rps15), four genes for photosystem protein subunits (psaA, psaJ, psbC, and pabK), two genes for ribosome protein large subunits (rpl22 and rpl32), and the clpP, infA, matK, rbcL, ycf1, and ycf2 genes. These gene regions may have played key roles in the adaptation of Dipsacales to diverse environments. In addition, phylogenetic analysis based on the plastid genomes strongly supported the division of 14 Dipsacales species into two previously recognized sections. The diversification of Adoxaceae and Caprifoliaceae was dated to the late Cretaceous and Tertiary periods. The availability of these chloroplast genomes provides useful genetic information for studying taxonomy, phylogeny, and species evolution in Dipsacales.